EU Accession to the ECHR: At the End of the Long and Winding Road? - Mohay, Ágoston (Pécs journal of international and European law, 2025)
Accession to the European Convention on Human Rights has been on the European Union’s agenda for decades. The Lisbon Treaty has removed the initial legal barriers, but actual accession has not been achieved to date: the reconciliation of the special characteristics of EU law with the Convention has proved to be a rather complex issue, illustrated well by Opinion 2/13 of the Court of Justice of the European Union (CJEU). The new draft accession agreement, which was drawn up during the relaunched negotiations, sought to address the issues raised by the Opinion 2/13, but questions remain, in particular regarding legal remedies in the Common Foreign and Security Policy (CFSP) as well as the EU law principle of mutual trust. Following an overview of the accession process so far, the paper concentrates on the analysis of these two selected issues, assessing the solutions included in (or indeed missing from) the 2023 draft.